2010
DOI: 10.1186/1471-244x-10-98
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from depressive symptoms, state anxiety and post-traumatic stress disorder in women exposed to physical and psychological, but not to psychological intimate partner violence alone: A longitudinal study

Abstract: BackgroundIt is well established that intimate male partner violence (IPV) has a high impact on women's mental health. It is necessary to further investigate this impact longitudinally to assess the factors that contribute to its recovery or deterioration. The objective of this study was to assess the course of depressive, anxiety and post-traumatic stress disorder (PTSD) symptoms and suicidal behavior over a three-year follow-up in female victims of IPV.MethodsWomen (n = 91) who participated in our previous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
88
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 65 publications
12
88
2
4
Order By: Relevance
“…Evidence of harassment, emotional, and physical abuse should warrant inquiry about suicidal ideation, given these abuse types were positively correlated with suicidal ideation and co-occur in both men and women (Black et al, 2011;Follingstad et al, 1990). Couples therapy is a critical setting in which both partners must be assessed for suicide risk because 71% of couples seeking therapy have been found to report IPV (Cascardi, Langhinrichsen, & Vivian, 1992). In particular, physical abuse should warrant careful assessment of suicidal ideation in men, whereas emotional abuse should warrant such assessment in women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Evidence of harassment, emotional, and physical abuse should warrant inquiry about suicidal ideation, given these abuse types were positively correlated with suicidal ideation and co-occur in both men and women (Black et al, 2011;Follingstad et al, 1990). Couples therapy is a critical setting in which both partners must be assessed for suicide risk because 71% of couples seeking therapy have been found to report IPV (Cascardi, Langhinrichsen, & Vivian, 1992). In particular, physical abuse should warrant careful assessment of suicidal ideation in men, whereas emotional abuse should warrant such assessment in women.…”
Section: Discussionmentioning
confidence: 97%
“…For example, emotional abuse persists despite the cessation of physical abuse in relationships and predicts repeated physical abuse (Jacobson, Gottman, Gortner, Berns, & Shortt, 1996). Emotional abuse is also cited by abused women as the primary reason for terminating abusive relationships because of painful psychological symptoms (i.e., posttraumatic stress disorder [PTSD], anxiety, and depression), that are difficult to recover from (Blasco-Ros et al, 2010;O'Leary, 1999). In addition, IPV characterized by emotional abuse may impact social factors, such as social support (Leone et al, 2007) or employment (Leone, Johnson, Cohan, & Loyd, 2004), which protect against suicidal ideation Kaslow et al, 1998).…”
Section: Intimate Partner Violence Types and Suicidal Ideation In Womenmentioning
confidence: 99%
“…One is that psychological abuse has severe consequences, since an abused woman's well-being usually deteriorates over time, often leading to loss of self-esteem and identity (Midlarsky et al 2006) and suppressed anger, depression, anxiety, and posttraumatic stress syndrome (Midlarsky et al;Swan and Snow 2003). Secondly, psychological abuse can also lead to other somatic problems such as sleep disturbances; fatigue; headaches; pains in chest, limbs, and back; respiratory problems; and menstrual difficulties (Blasco-Ros et al 2010;Sutherland et al 2001;Svavarsdottir andOrlygsdottir 2009). Blasco-Ros et al (2010) also found that women who were exposed to psychological abuse needed more time to escape from the abuse and were less likely to recover their mental health.…”
Section: Extent Of Abusementioning
confidence: 97%
“…Recently, Blasco-Ros, Sánchez-Lorente, and Martinez (2010), investigated the recovery of PTSD over a 3-year period in a community sample of 91 IPV victims. They found that women exposed to both physical and psychological IPV experienced significant reduction in both incidence (24.2%–18.2%) and severity of PTSD over follow-up, whereas those with only psychological IPV did not experience significant recovery from PTSD.…”
mentioning
confidence: 99%
“…None of the studies, however, specifically investigated factors related to remission of IPV-related PTSD. Other limitations include use of a self-report measure of PTSD, no inclusion of baseline and follow-up rates of PTSD (Krause et al, 2008), low rates of PTSD, inclusion of only one follow-up period, and failure to account for sub-threshold PTSD symptoms (Blasco-Ros et al, 2010; Mertin & Mohr, 2001), lack of specification regarding if the PTSD was IPV-related, and failure to assess for correlates of recovery from PTSD (Mertin & Mohr, 2001). Thus, more longitudinal research on IPV-related PTSD is warranted, especially for IPV victims who seek shelter to establish safety.…”
mentioning
confidence: 99%